Traços de personalidade como preditores de ansiedade e agressividade em grupos contrastados: clínico e não clínico - Silva, Jussara Ramos da (2013)
This work is the result of a correlational study and a comparison between participants in order to set dates in which were considered two main sets of variables: criterion (aggressiveness behavior) and background (clinical and non-clinical situation - anxiety diagnostic and neuroticism degree), and it aimed to investigate the influence of personality traits, especially neuroticism, in levels of anxiety and aggressiveness displayed in contrasted groups (clinical and non-clinical). This research relied on a sample of 113 subjects, 49 (43.4%) males and 64 (56.6%) females, aged from 18 to 57 years old (M = 25,32, DP = 8,80) and it was used three psychometric scales of measurement: IGFP-5, STAXI-2 and BAI. The data’s collection occurred in two Federal Public Universities from different Capitals, in Maceió city and Belo Horizonte city (non-clinical group), and also in School Clinics and Private Clinics in Maceió city (clinical group). On the personality traits theory, specifically the one of The Big Five Personality Factors (BFF) or Big Five, it’s focused, in special, the "neuroticism" trait, following with the correlation of this one and the constructs "anxiety", as an emotional modulation factor, and "aggressiveness." It is a study in the Cognitive Psychology area, through the integration of individual differences in relation to statistical and psychobiological factors, assuming that personality traits, having them genetic factors in connection with environmental aspects, overlap themselves and are responsible for the maturation and constant flexibility on the personality development, taking three important functions: summarize the way how individuals differ, to predict future behavior and to explain a person’s conduct, as an anxious or aggressive behavior, for example. The neuroticist trace predicts in the individual, in this context, at a high level, abrupt, frequent and dramatic mood changes, especially in negative character, possibly by being among other things related to insufficient function in some specific brain areas that are involved with negative emotion and emotional deregulation, anxiety, stress and depression, besides it provides the increase of sensitivity to the error possibility, threat and punishment. The conclusions point to the fact that neuroticism (IGFP-5) is positively correlated with anxiety (BAI) and some questions of the aggressiveness (STAXI-2) and especially (inversely) with the aggressive response control (outwards and inwards), which can be related to impulsivity, in other words, inability in the inhibitory control. It appears that despite advances on the studied area, new models of research with interdisciplinary protocols may bring new answers to this issue, seeking a larger field for the psychology professional about the differences, advantages and similarities between the personality theories presented and their role models, and a more powerful qualification with interconnection of knowledge focusing on this theme, such in neuropsychological, genetic, psychological and by functional imaging (neuroimaging), as in a bigger connection between executive functions, personality traits and behavioral changes, for example.